Field notes and letter to Thomas H. Kent contributed by Peter Ernzen, fall 1997 - Ernzen, Peteret al (1997)
Fall report of birds contributed by Peter Ernzen. Also included is a letter from Ernzen to Thomas H. Kent regarding a Pine Grosbeak sighting reported by Curtis L. Rector. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1997. Epson - sheet feed